PENGELOLAAN PEMBELAJARAN KEWIRAUSAHAAN DI UNIVERSITAS NEGERI PADANG - LUTFI LUTFI (Universitas Negeri Padang, 2016)
The purpose of this research are: (1) to know about the planning of entrepreneurial learning at Padang State University, (2) to know about the implementation of entrepreneurial learning at Padang State University, and (3) to know about the evaluation of entrepreneurial learning at Padang State University.This is quantitative research that conducted in Padang State University. Data collection technique used questionnaire with Likert Scale models that have been tested for validity and reliability. Furthermore, the data is processed through search analytics average value (the mean). The results of the research show that: (1) The planning of entrepreneurial learning at Padang State university is good. (2) The implementation of entrepreneurial learning is good and(3)The evaluation of entrepreneurial learning at Padang State University is good.